Effectiveness and initial outcomes of transvesicoscopic bipolar sealing of vesicovaginal fistula - Akkoç, Ali; Aydın, Cemil (Journal of Surgery and Medicine, 2020)
Aim: Vesicovaginal fistula (VVF) is a social and psychological problem for the female population, causing urinary incontinence and foul-smelling urine. Open, laparoscopic, robotic, and various minimally invasive techniques have been described for the treatment of VVF. In this study, we presented the effectiveness and initial outcomes of transvesicoscopic bipolar sealing of vesicovaginal fistula (TBSF), a novel, minimally invasive technique which we had previously described. Methods: This surgical case series included 9 patients with VVF of <1 cm located away from ureteral orifices who underwent TBSF from July 2015 to December 2019. The fistula tract was sealed transvesicoscopically with a bipolar vessel sealer. All patients were informed about the modified surgical procedure prior to the operation. Results: The mean age of the patients was 47.2 (4.6) years. The mean fistula diameter was 6.6 (1.2) mm. The mean operation time was 41 (9.7) minutes. The hospital stay was 1 day in all cases. After catheter removal at 3 weeks, 8 (89 %) patients remained dry while one (11%) patient experienced continuous incontinence. Conclusion: Transvesicoscopic bipolar sealing of vesicovaginal fistula is a simple and safe procedure to perform for small VVF, has a short learning curve and operative time, and results in reduced blood loss and morbidity, brief hospital stay and improved cosmesis.